MASTERY OF SWIMMING TECHNIQUES FREE STYLE USING THE PART METHOD IN ELEMENTARY SCHOOL STUDENTS - Sandra Arhesa; Amung Ma'mum (Universitas Majalengka, 2023)
The background of this research is the lack of mastery of freestyle swimming technique skills for elementary school beginner swimmers that are not in accordance with the correct technique at the Arhesa Swimming Club. The purpose of this study was to improve mastery of the freestyle swimming technique using the part method for elementary school students. The method used in this study was experimental, using a quasi-experimental design in the form of a One-Group Pretest-Posttest Design. The population in this study were elementary school students at the Arhesa Swimming Club, namely 10 people. The sampling technique in this study used total sampling, with a sample of 10 elementary school students. The research instrument used the Freestyle Swimming Skills Assessment Test. Data analysis tested the mean and standard deviation, normality test, homogeneity test, and hypothesis testing, namely the Paired Sample Test using SPSS 25. Based on the results of the analysis t count is less than t table (11.00 < 1.83) then Ho is rejected, meaning that there is an increase in the initial test towards the final test of freestyle swimming technique mastery, with this it can be concluded that the Part Method can improve technique mastery freestyle swimming in elementary school students. Penelitian ini dilatarbelakangi oleh kurangnya penguasaan keterampilan teknik renang gaya bebas perenang pemula sekolah dasar yang tidak sesuai dengan teknik yang benar di Arhesa Swimming Club. Tujuan penelitian ini untuk meningkatkan penguasaan teknik renang gaya bebas menggunakan part method pada siswa sekolah dasar. Metode yang digunakan dalam penelitian ini adalah eksperimen, dengan menggunakan quasi-experimental design dalam bentuk One-Group Pretest-Posttest Design. Populasi dalam penelitian ini adalah siswa sekolah dasar yang ada di Arhesa Swimming Club, yaitu 10 orang. Teknik Sampling dalam penelitian ini menggunakan Total Sampling, dengan sampel sebanyak 10 siswa sekolah dasar. Instrumen penelitian menggunakan Tes Penilaian Keterampilan Renang Gaya Bebas. Analisis data menguji rata-rata dan simpangan baku, uji normalitas, uji homogenitas, dan uji hipotesis yaitu Paired Sample Test menggunakan SPSS 25. Berdasarkan hasil analisis t hitung kurang dari t tabel (11,00 < 1,83) maka Ho ditolak, artinya ada peningkatan tes awal terhadap tes akhir penguasaan teknik renang gaya bebas, dengan ini maka dapat disimpulkan bahwa dengan adanya Part Method dapat meningkatkan penguasaan teknik renang gaya bebas pada siswa sekolah dasar.